Towards a unified approach to sciences and the arts - Athanassios S. Fokas (Proceedings (European Academy of Sciences and Arts))
The process of ‘comprehending how we comprehend’, requires elucidating fundamental cognitive mechanisms used by the brain. In these regards, this article discusses two basic hypotheses. First, unconscious and conscious processes form a continuum. Second, humans have a predisposition to construct real versions of mental images and of unconscious structures, as well as to assign to them specific symbols. In addition, it is claimed that our process of comprehending is aided by invoking certain concepts which are important because, apparently, they reflect fundamental cognitive mechanisms. Among them are the notions of continuity, associations, abstraction, reduction, unification, and generalization, as well as the dialectic pairs of local versus global processes and simplicity versus complexity.